Therapeutic Potential of Exploiting Autophagy Cascade Against Coronavirus Infection - Maity, Subhajit; Saha, Abhik (Frontiers in Microbiology, 2021)
Since its emergence in December 2019 in Wuhan, China, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) created a worldwide pandemic of coronavirus disease (COVID-19) with nearly 136 million cases and approximately 3 million deaths. Recent studies indicate that like other coronaviruses, SARS-CoV-2 also hijacks or usurps various host cell machineries including autophagy for its replication and disease pathogenesis. Double membrane vesicles generated during initiation of autophagy cascade act as a scaffold for the assembly of viral replication complexes and facilitate RNA synthesis. The use of autophagy inhibitors - chloroquine and hydroxychloroquine initially appeared to be as a potential treatment strategy of COVID-19 patients but later remained at the center of debate due to high cytotoxic effects. In the absence of a specific drug or vaccine, there is an urgent need for a safe, potent as well as affordable drug to control the disease spread. Given the intricate connection between autophagy machinery and viral pathogenesis, the question arises whether targeting autophagy pathway might show a path to fight against SARS-CoV-2 infection. In this review we will discuss about our current knowledge linking autophagy to coronaviruses and how that is being utilized to repurpose autophagy modulators as potential COVID-19 treatment.